CEREBRAL STROKE: CRITERIA OF TRANSFR TO ALV AND ASSISTED VENTILATION - E. V. ELISEEV; D. A. DOROSHENKO; T. Y. NEDOROSTKOVA; G. R. KUCHAVA; N. V. KRIVOSHEEVA; A. R. ZUBAREV (Медицинский совет, 2016)
Analysis of outcomes in 211 patients with acute cerebral stroke hospitalized in the neuro rehabilitation in Filatov Municipal Clinical Hospital No. 15 of Mos cow in 2012-2013 who received artificial lung ventilation (ALV) due to respiratory disturbances was performed. Laboratory criteria and terms of patient transfer to ALV at acute stroke were detected. It was established that a riterion of patients transfer to AL V is not only manifestation of respiratory insufficiency clinical pattern but indicators of acid-base blood state. Objective clinical and laboratory criteria allowing timely transfer to ALV and forec ast of the unfavourable outcome are set out.